2016
DOI: 10.3390/ijms17091582
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-Induced Variation in Biochemical Markers Provides Insight into the Mechanisms of Salt Tolerance in Common (Phaseolus vulgaris) and Runner (P. coccineus) Beans

Abstract: The evaluation of biochemical markers is important for the understanding of the mechanisms of tolerance to salinity of Phaseolus beans. We have evaluated several growth parameters in young plants of three Phaseolus vulgaris cultivars subjected to four salinity levels (0, 50, 100, and 150 mM NaCl); one cultivar of P. coccineus, a closely related species reported as more salt tolerant than common bean, was included as external reference. Biochemical parameters evaluated in leaves of young plants included the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 48 publications
6
33
2
3
Order By: Relevance
“…We have selected three cultivars of Phaseolus vulgaris and one cultivar of its congener P. coccineus, to perform a comparative analysis of the responses of the plants to water deficit treatments under controlled greenhouse conditions. This work extends and complements a previous study where different responses of the same cultivars to salt stress treatments were investigated (15). Here, we have focused on a basic, conserved mechanism activated in plants subjected to different abiotic stresses, including drought; namely, the synthesis and accumulation of specific osmolytes (proline, glycine betaine or soluble carbohydrates) to maintain cellular osmotic balance, which is disrupted under stress conditions.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…We have selected three cultivars of Phaseolus vulgaris and one cultivar of its congener P. coccineus, to perform a comparative analysis of the responses of the plants to water deficit treatments under controlled greenhouse conditions. This work extends and complements a previous study where different responses of the same cultivars to salt stress treatments were investigated (15). Here, we have focused on a basic, conserved mechanism activated in plants subjected to different abiotic stresses, including drought; namely, the synthesis and accumulation of specific osmolytes (proline, glycine betaine or soluble carbohydrates) to maintain cellular osmotic balance, which is disrupted under stress conditions.…”
Section: Introductionsupporting
confidence: 66%
“…The soluble sugar fraction (mono-and oligosaccharides) was analysed using a Waters 1525 high performance liquid chromatography coupled to a 2424 evaporative light scattering detector (ELSD), as previously described (15). Standards of glucose, fructose, sucrose, and myo-inositol were used to identify peaks by co-injection.…”
Section: Hplc Analysismentioning
confidence: 99%
“…When comparing ion levels between roots and needles, no differences were observed in Na + contents (in terms of DW), neither in control nor in salt-stressed seedlings; regarding Cl − , its concentration was slightly (but significantly) higher in needles than in roots, again in both non-stressed and salt-stressed seedlings. These results indicate that European larch responses to salinity do not include mechanisms blocking the transport of toxic ions from underground to aboveground parts of the plants, contrary to what has been described for most glycophytic taxa, including many crops [57,62], or for halophytic monocotyledonous species [63].…”
Section: Ion Homeostasiscontrasting
confidence: 49%
“…These mechanisms appear to be constitutive, since these ions were present at high concentrations also in the leaves of nonstressed plants. The accumulation of high leaf Na + concentrations under low soil salinity conditions has been described for several halophytes, both in field [54] and greenhouse [111] experiments, and also (to a lesser extent) in typical glycophytes, such as some Phaseolus cultivars [20]. In S. vulgaris, specific mechanisms of tolerance to salinity seem to be based on the inhibition of additional transportation of toxic ions to the aerial parts of the plants, whereas accumulation of soluble sugars may contribute to tolerance to drought.…”
Section: Discussionmentioning
confidence: 90%
“…Lately, however, more emphasis is being placed on deciphering stress response mechanisms of some minor crops and many wild species with a wide spectrum of tolerance, some of them closely related to crop and model plant species. Some of these studies have found differences in the efficiency of stress responses in closely related species, or in different cultivars, ecotypes, or even individual populations of the same species [20].…”
Section: Introductionmentioning
confidence: 99%